ASSESSMENT OF THE DIETARY ENERGY INTAKE OF YOUNG PEOPLE WITH NORMAL WEIGHT AND OVERWEIGHT - Vesnina, L.E.; Boriak, Kh.R.; Sokolenko V.М. (World of Medicine and Biology, 2020)
The problem of weight gain and obesity with the formation of energy imbalance remains relevant especially among children and young people. The paper was aimed at determining the dietary energy intake of young people with normal weight and overweight and its compliance with energy needs. The study involved 84 male and female subjects aged 18-25. Height, body weight, waist circumference, and thighs circumference, and their ratio was determined. According to the body mass index (BMI), 22 women and 22 men (BMI 18.50-24.99 kg/m2) have been assigned to the control group and the group with overweight involved 20 men and 20 women (BMI 25.00-29.99 kg/m2). Nutritional status has been studied by the method of 24-hour nutrition reproduction by making records in the food diary during a weekday and weekend day. The value of the basal metabolic rate was calculated by the Mifflin-St Jeor equation. Was determined the recommended daily energy dietary intake maintains the existing body weight. The obtained data were processed statistically. The development of energy imbalance in people with overweight of both genders, a significant increase in the energy value of the dietary intake compared to controls and in comparison with the recommended daily energy intake has been established. The increase in energy value is accompanied by the altered structure of nutrients due to increased consumption of mainly fats by male subjects with overweight and fats and carbohydrates by female subjects compared to the controls. In men of the control group, the increase in energy value of the dietary intake relative to the recommended daily energy intake is less pronounced compared to subjects with overweight. Prolonged existence of the positive energy balance is the risk factor for the development of obesity and metabolic disorders.